Evidence of Marine Microplastics in Commercially Harvested Seafood - Curren, Emily; Leaw, Chui Pin; Lim, Po Teen; Leong, Sandric Chee Yew (Frontiers in Bioengineering and Biotechnology, 2020)
Microplastic pollution is a global issue that has a detrimental impact on food safety. In marine environments, microplastics are a threat to marine organisms, as they are often the same size range as prey and are mistaken as food. Consumption of microplastics has led to the damage of digestive organs and a reduction in growth and reproductive output. In this study, microplastic pollution was assessed across three commercially available shrimp species that were obtained from the supermarkets of Singapore. A total of 93 individuals were studied from the Pacific white leg shrimp, Litopenaeus vannamei, the Argentine red shrimp Pleoticus muelleri and the Indian white shrimp Fenneropenaeus indicus. Microplastic fibers, fragments, film and spheres were identified from the digestive tract of these organisms. Microplastic abundance ranged from 13.4 to 7050 items (g.w.w.). F. indicus exhibited the highest number of microplastics. Microplastic film was the most abundant in L. vannamei individuals (93-97%) and spheres were the most abundant in P. muelleri (70%) and F. indicus (61%) individuals. This study demonstrates that microplastic contamination is evident in commonly consumed shrimp and highlights the role of shrimp in the trophic transfer and accumulation of microplastics in seafood. The consumption of microplastic-containing seafood is a route of exposure to humans and has implications on human health and food security.